Rheological and physical properties of various flour extrudates at different barrel temperatures - Lim, Sue Shan (2016)
Extrusion process is a high-temperature short time cooking process. The aim of this study was to evaluate the effect of barrel temperature and flour types on the residence time distribution, physical properties and rheological properties of various pregelatinized flour. Corn flour, rice flour, and their blends with 30% potato starch (w/w, d.b), were extruded under extrusion conditions at screw speed of 75 rpm, feed moisture at 25% (w/w, w.b.), barrel temperature ranging from 80 °C to 140 °C and die size of 1.88 mm. The extrudates were dried at 50 °C overnight, ground and further analyzed. The results showed that an increase in extruder barrel temperature significantly decreased the mean residence time (p ≤0.05), total collection time (p ≤0.05) and mean collection time (p ≤0.05) of the extrudates. Analysis on the physical properties (expansion ratio, rehydration ratio, water absorption index, water solubility index, color, and water activity) and the rheological properties (steady shear, dynamic shear, and cohesiveness of powder) were done on the extrudate sample. The results showed that increase in barrel temperature significantly increased expansion ratio (p ≤0.05), water absorption index, WAI (p ≤0.05), water solubility index, WSI (p ≤0.05), and the yellowness, b (p ≤0.05) of the extrudates while decreased the shear thinning behavior (n become closer to 1), and decreased the apparent viscosity of the extrusion dispersion at shear rate 100 s-1. The addition of potato starch influences the properties such as increases the WSI at 140°C, decreases the WAI at 140°C and decreases the overall gel strength of the pregelatinized flours. Corn flour blended with potato starch extrudates and rice flour extrudates were well fitted (R2 >0.8) into the Arrhenius equation with a decreasing Ea with increasing extruder barrel temperature. All extrudate samples showed shear thinning behavior for the dispersion and a solid-like gel. The additional of potato starch on the extrudates extruded barrel temperature of 80 °C and 100 °C make the extrudates less frequency dependency with a moderate but consistent G´ across the frequency range tested. The addition of potato starch caused properties different such as an increase in WAI, WSI and decrease in overall G´ and G˝ of the pregelatinized flours. The pregelatinized flours’ cohesiveness was not affected by barrel temperature (p >0.05). Corn flour blended with potato starch extrudates showed a good thickening and gelling properties. Both, the effects of barrel temperature and flour type play important roles in the rheological and physical properties of the pregelatinized flours.